Patterns of regulatory behavior in the still-face paradigm at 3 months: A comparison of Brazilian and Portuguese infants - Fuertes, Marina (2022)
Three infant regulatory behavior patterns have been identified during the Face-to-Face Still- Face paradigm (FFSF) in prior research samples: a Social-Positive Oriented pattern (i.e., infants exhibit predominantly positive social engagement), a Distressed-Inconsolable pattern (i.e., infants display conspicuous negative affect that persists or increases across FFSF episodes), and a Self-Comfort Oriented pattern (e.g., infants primarily engage in self-comforting behaviors such as thumb-sucking). However, few studies have examined these patterns outside US and European countries or evaluated potential cross-country differences in these patterns. In this study, we compared the regulatory behavior patterns of 74 Brazilian and 124 Portuguese infants in the FFSF at 3 months of age, and evaluated their links to demographic and birth variables. The prevalence of the three regulatory patterns varied by country. The most frequent pattern in the Portuguese sample was the Social-Positive Oriented, followed by the Distressed-Inconsolable and the Self-Comfort Oriented. However, in the Brazilian sample, the Distressed-Inconsolable pattern was the most prevalent, followed by the Social- Positive Oriented and the Self-Comfort Oriented. Moreover, in the Brazilian sample, familial SES was higher among infants with a Social-Positive pattern whereas 1st-minute Apgar scores were lower among Portuguese infants with a Distressed-Inconsolable Oriented pattern of regulatory behavior. In each sample, Social Positive pattern of regulatory behavior was associated with maternal sensitivity, Self-Comfort Oriented pattern of regulatory behavior with maternal control, and Distressed-Inconsolable pattern with maternal unresponsivity.